2009
DOI: 10.1177/030089160909500322
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Melanocytoma: Case Report and Review of Literature

Abstract: We report on a very rare case of dorsal intramedullary melanocytoma in a 62-year-old man. The tumor was resected and gross total removal was achieved. During a 2-year follow-up period in which no radiotherapy was given, the tumor did not recur. We review the literature on these tumors and present disease criteria to distinguish melanocytoma from primary malignant melanoma. Patients and investigators should be cautioned that an intramedullary melanocytoma may recur and give rise to metastatic spread via the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…4 This tumour is most commonly found in women with an average age of 43 years (range, 19-79 years). Meningeal melanocytomas are derived from leptomeningeal melanocytes; thus, most of the spinal lesions are intradural and extramedullary in location.…”
Section: Discussionmentioning
confidence: 99%
“…4 This tumour is most commonly found in women with an average age of 43 years (range, 19-79 years). Meningeal melanocytomas are derived from leptomeningeal melanocytes; thus, most of the spinal lesions are intradural and extramedullary in location.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three cases ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , Table 1) of spinal intramedullary melanocytomas have been reported in the literature since 1993; we add a further case description of this rare tumor entity. We would like to point out that Iida et al ( 4 ) reported two cases with spinal melanocytoma—one intradural extramedullary located and the other intramedullary manifested—and we review only the one case with the intramedullary tumor.…”
Section: Discussionmentioning
confidence: 95%
“…Primary melanocytic neoplasms of the meninges (meningeal melanocytomas) are uncommon neoplasms of the central nervous system; only 23 cases have been published up to now ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ; Table 1). These neoplasms may occur in a diffuse or localized form ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 , 6 , 7 , 8 , 9 These intramedullary variants derive from melanocytes of the parenchymal perivascular spaces, also known as Virchow-Robin spaces, and occur most commonly in the lower thoracic spinal cord. 5 , 10 …”
mentioning
confidence: 99%